Jean-François Bony (Givors, 1754-Paris, 1827) : tentures brodées et panneaux peints - Danièle Véron-Denise (Bulletin du Centre de Recherche du Château de Versailles)
Jean-François Bony is a multi-faceted artist whose talent has been expressed in painting as well as in the textile arts in general and embroidery in particular. He designed the clothes worn by Josephine at the coronation of Napoleon I in 1804. He also received prestigious commissions for several royal and imperial residences. Of all his works, his masterpiece is undoubtedly the magnificent hanging commissioned in 1811 from Bissardon Cousin et Bony for Marie-Louise’s appartment in Versailles. On a white satin background, a variety of bouquets and fabulous birds embroidered in silk have retained all the freshness and appeal of their original colours. In a similar vein, a five-piece hanging at the Museum of Decorative Arts in Madrid also bears witness to his decorative skills, as does another large embroidered piece at the Gulbenkian Foundation in Lisbon. It has also been possible to attribute wood panelling with arabesque decoration to Bony, notably that found in the boudoir of the Chaumière aux Coquillages in the Parc de Rambouillet. There is no doubt that the list of works by this prolific and talented artist could be extended…